2009
DOI: 10.1007/s00259-009-1332-5
|View full text |Cite
|
Sign up to set email alerts
|

Dose-response assessment of tariquidar and elacridar and regional quantification of P-glycoprotein inhibition at the rat blood-brain barrier using (R)-[11C]verapamil PET

Abstract: Purpose-Overactivity of the multidrug efflux transporter P-glycoprotein (P-gp) at the bloodbrain barrier (BBB) is believed to play an important role in resistance to central nervous system drug treatment. (R)-[ 11 C]verapamil (VPM) PET can be used to measure the function of P-gp at the BBB, but low brain uptake of VPM hampers the mapping of regional differences in cerebral P-gp function and expression. The aim of this study was to evaluate the dose-response relationship of two potent P-gp inhibitors and to inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
136
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(157 citation statements)
references
References 25 publications
18
136
3
Order By: Relevance
“…Both clinical and preclinical studies have reported small, but significant, regional differences in increasing concentrations of the P-gp substrate radiotracer (R)-11 Cverapamil after P-gp inhibition (16,34,35). In contrast, effects of tariquidar on Q out and V br were similar in all brain regions studied in the present study (Table 4).…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…Both clinical and preclinical studies have reported small, but significant, regional differences in increasing concentrations of the P-gp substrate radiotracer (R)-11 Cverapamil after P-gp inhibition (16,34,35). In contrast, effects of tariquidar on Q out and V br were similar in all brain regions studied in the present study (Table 4).…”
Section: Discussioncontrasting
confidence: 50%
“…Tariquidar, 3 (n 5 6) or 15 (n 5 23) mgÁkg 21 , was administered as an infusion over 10 min, starting 20 min before the second scan. The tariquidar doses were based on studies showing that 15 mg/kg results in complete inhibition of P-gp and 3 mg/kg is close to the median effective dose (16). The lower dose of 3 mg/kg can also be used in humans and could potentially allow for the translation of results between preclinical and clinical studies.…”
Section: Pet Experimentsmentioning
confidence: 99%
“…The choice of loperamide as a P-gp substrate and its dose was based on its opiate-like behavior, which provides an efficient means with which to ascertain the blockage of the P-gp (Elkiweri et al, 2009). Because the reported ED 50 values for tariquidar and elacridar in rats (Kuntner et al, 2010) were lethal in coadministration with loperamide in our pilot study, the doses of the P-gp modulators were reduced to 0.5 or 1.0 mg/kg.…”
Section: Methodsmentioning
confidence: 99%
“…Elacridar is a third-generation P-gp inhibitor with K i of 1.6 nM for P-gp inhibition and is also a potent Bcrp inhibitor with in vitro EC 90 of 51 to 61 nM (Allen et al, 2002;Sugimoto et al, 2011). Its in vivo mouse and rat plasma IC 50 for inhibition of P-gp at the BBB ranged from 114 to 282 ng/ml, and its IC 50 for inhibition of Bcrp was 790 ng/ml determined in a brain perfusion study (Cutler et al, 2006;Bihorel et al, 2007;Oostendorp et al, 2009;Kuntner et al, 2010;Sugimoto et al, 2011). Thus, with 2-fold as a cutoff value for the effects of elacridar on K p , no change for the K p values of P-gp and/or Bcrp substrates occurs when elacridar plasma concentrations are below 114 ng/ml.…”
Section: Liu Et Almentioning
confidence: 99%